Orienting virtue : civic identity and orientalism in Britain's global eighteenth century - Williamson, Bethany, 1985- (University of Virginia Press, 2022)
"This book examines how British writers in the eighteenth century deployed images of the East to shape ideas of virtue and political identity"--